First clinical postmarketing experiences in the treatment of epilepsies with brivaracetam: A retrospective observational multicentre study - Menzler, Katja; Mross, Peter Michael; Rosenow, Felix; Schubert-Bast, Susanne; Willems, Laurent Maximilian; Zahnert, Felix; Immisch, Ilka; Fuest, Sven; Von Podewils, Felix; Kunz, Rhina; Hirsch, Martin; Müller, Tamara; et al. (BMJ Open, 2019)
Objectives Brivaracetam (BRV) is the latest approved antiepileptic drug and acts as a synaptic vesicle protein 2A ligand. The aim of the present study was to evaluate the efficacy and tolerability of BRV in the clinical setting. Design Retrospective, observational multicentre study. Setting We retrospectively collected clinical data of patients who received BRV in 10 epilepsy centres using a questionnaire that was answered by the reporting neurologist. Participants Data of 615 epilepsy patients treated with BRV were included in the study. Primary and secondary outcome measures Efficacy regarding seizure frequency and tolerability of BRV were evaluated. Descriptive statistics complemented by X 2 contingency tests and effect sizes were performed. Results Overall, 44% of the patients had a decreased, 38% a stable and 18% an increased seizure frequency. 17% of patients achieved seizure freedom after initiation of BRV. The seizure frequency decreased in 63% of 19 patients with BRV monotherapy. 27% reported adverse effects, but only 10% of patients with monotherapy. Brivaracetam was significantly more often associated with decreased seizure frequency in levetiracetam (LEV) naïve patients (p=0.012), but BRV also led to a decreased seizure frequency in 42% of patients who had been treated with LEV before, including 17% of patients who were completely seizure free. Adverse effects under LEV improved in 62% and deteriorated in 2% of patients after the switch to BRV. At latest follow-up (mean±SD = 26.3±6.5 months), 68% were still on BRV. Conclusions The present study shows that results of the phase III studies on BRV match data from real life clinical settings. Brivaracetam seems to be a useful alternative in patients who have suffered adverse effects while taking LEV.
CRIS-Team Scopus Importer:2019-11-15
Keywords: adverse events; brivaracetam; efficacy; levetiracetam; monotherapy; tolerability